GU-Journal - Språkbanken Text (University of Gothenburg, 2025)
GU Journalen is the University of Gothenburg's newspaper for employees and students. It serves as an internal
publication that reports on news, research, and events within the university.
In addition to articles from GU Journalen, the corpus also includes newsletters from 1995-1997, which are a
predecessor to GU Journalen.

GU Journalen är Göteborgs universitets tidning för anställda och studenter. Den fungerar som en intern
publikation som rapporterar om nyheter, forskning och händelser inom universitetet.
Utöver artiklar från GU Journalen innehåller korpusen även nyhetsbrev från 1995-1997 som är en föregångare till GU
Journalen.
GU Journalen
Keywords: Language Technology (Computational Linguistics); magazines; news texts; non-fiction; corpus; Natural Language Processing; Språkbehandling och datorlingvistik